Qualitative Analysis of Polyphenols in Macroporous Resin Pretreated Pomegranate Husk Extract by HPLC‐QTOF‐MS. Issue 5 (23rd June 2017) - Abdulla, Rahima; Mansur, Sanawar; Lai, Haizhong; Ubul, Ablikim; Sun, Guangying; Huang, Guozheng; Aisa, Haji Akber
Abstract: Introduction: Pomegranate ( Punica granatum L.) husk is a traditional herbal medicine abundant in phenolic compounds and plays some roles in the treatment of oxidative stress, bacterial and viral infection, diabetes mellitus, and acute and chronic inflammation. Objective: Identification and determination of polyphenols in macroporous resin pretreated pomegranate husk extract by high performance liquid chromatography coupled with quadrupole time‐of‐flight tandem mass spectrometry (HPLC‐QTOF‐MS). Methods: The total polyphenols of pomegranate husk were prepared by ethanol extraction followed by pretreatment with HPD‐300 macroporous resin. The polyphenolic compounds were qualitatively analysed by HPLC‐QTOF‐MS in negative electrospray ionisation (ESI) mode at different collision energy (CE) values. Results: A total of 50 polyphenols were detected in the extract of pomegranate husk, including 35 hydrolysable tannins and 15 flavonoids with distinct retention time, fragmentation behaviours and characteristics, and the accurate mass‐to‐charge ratios at low, moderate and high CE values. Of these, we identified nine compounds for the first time in the pomegranate husk, including hexahydroxydiphenoyl‐valoneoyl‐glucoside (HHDP‐valoneyl‐glucoside), galloyl‐ O ‐punicalin, rutin, hyperoside, quercimeritrin, kaempferol‐7‐ O ‐rhahmano‐glucoside, luteolin‐3′‐ O ‐arabinoside, luteolin‐3′‐ O ‐glucoside, and luteolin‐4′‐ O ‐glucoside. To validate the specificity and accuracy of mass spectrometry in the detection of polyphenols, as compared to the fragmentation pathways of granatin B in detail, including the HHDP‐valoneyl‐ glucoside was first identified from pomegranate husk. Conclusion: The study provides evidence for the quality control and development of novel drugs based on polyphenols from the pomegranate husk. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : In this study, 35 hydrolysable tannins and 15 flavonoids as polyphenols were detected in the extract of the Punica granatum L. husk, of which 9 compounds newly identified, by separation with HPD‐300 macroporous resin followed by analyses on the HPLC‐QTOF/System. In addition, the accuracy and specificity of mass spectrometric detection were validated by detailed analysis of fragmentation pathways for two major polyphenolic compounds. The study provides evidence for the quality control and drug development based on the Punica granatum L. husk, a traditional herbal medicine.